Small-scale processing of fish - International Labour Office; United Nations Industrial Development Organisation (Geneva : International Labour Office, 1982)
This book covers a large range of fish processing techniques, various species of fish, methods of preserving fish, fish products for small-scale producers in developing countries.
Includes bibliography
gp. 22/01/2019
Loans
Keywords: Geneva